1997
DOI: 10.1046/j.1365-2125.1997.05382.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochromes P450 mediating the N‐demethylation of amitriptyline

Abstract: Aims Using human liver microsomes and heterologously expressed human enzymes, we have investigated the involvement of CYPs 1A2, 2C9, 2C19, 2D6 and 3A4 in the N-demethylation of amitriptyline (AMI), with a view to defining likely influences on its clinical pharmacokinetics. Methods The kinetics of formation of nortriptyline (NT) from AMI were measured over the substrate concentration range 1-500 mm, using liver microsomes from four extensive metabolisers (EM) and one poor metaboliser (PM) with respect to CYP2D6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…However, our study suggests that the affinity of amitripty line for CYP 2C 19 is more than 10 times high er than that of mephenytoin (Km 13 pmol/1 compared to Km values in the range of 200-300 pmol/1 for mephenytoin as reported by Hall et al [14]). Thus, no measurable inhibi tion is expected to take place in the experi ment designed by Ghahramani et al [9]. An analogous problem has occurred with regard to in vitro studies on imipramine N-demethylation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, our study suggests that the affinity of amitripty line for CYP 2C 19 is more than 10 times high er than that of mephenytoin (Km 13 pmol/1 compared to Km values in the range of 200-300 pmol/1 for mephenytoin as reported by Hall et al [14]). Thus, no measurable inhibi tion is expected to take place in the experi ment designed by Ghahramani et al [9]. An analogous problem has occurred with regard to in vitro studies on imipramine N-demethylation.…”
Section: Discussionmentioning
confidence: 94%
“…Ghahramani et al [9] found support for involvement of CYP 3A4. 2C9 and 2D6 on the basis of hepatic microsomal studies with selective inhibition of CYP isoforms, but were unable to establish a role for 2C19, which one should have ex pected from the cited in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CYP2D6 can metabolizes progesterone (8) and pregnenolone (9), and Guengerich et al have recently described a spirosulphonamide as a high affinity substrate of CYP2D6, which lacks a basic nitrogen (10). Furthermore, the enzyme can catalyze N-dealkylation reactions of substrates such as deprenyl (11), amitriptyline (12), methamphetamine (13), the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (14), and dextromethorphan (15), a commonly used antitussive.…”
mentioning
confidence: 99%
“…The liver metabolism considered amitriptyline biotransformation by CYP isoforms 1A2, 2B6, 2C8, 2C9, 2C19, 2D6, and 3A43435. The values of the maximal rate of saturating substrate concentrations (Vmax), Michaelis constants (Km) and Inter System Extapolation Factors (ISEF) used in the model are reported in the Table (4).…”
Section: Methodsmentioning
confidence: 99%
“…Values are after34. † Denotes another source of data i.e.,35.ISEF values correspond to B-Cell Lymphoma model and are taken from Simcyp Simulator.…”
Section: Figurementioning
confidence: 99%